Development and Clinical Uses of a Mobile Application for Smart Wound Nursing Management. (June 2021) - Zhang, Qijian; Huang, Weihong; Dai, Weiwei; Tian, Hanzhang; Tang, Qiongfang; Wang, Shihui
ABSTRACT: OBJECTIVE: Establishing a smart platform for wound nursing management is imperative to accelerating the development of this specialty. A mobile application (app) was created based on the clinical needs of wound care to improve working efficiency and wound management, as well as enable information sharing and categorical retrieval of patient records. METHODS: Supported by the National Mobile Laboratory of China, the authors' wound care center collaborated with information technology engineers and user interface designers to establish a multidisciplinary team of experts in wound nursing information management and develop a digital app. Electronic tablets were chosen as a convenient clinical method to collect complete information in a standardized format. In the app, case records are synchronously cataloged for rapid retrieval. The app was designed such that practicing nurses could quickly learn how to use the various functions of the app. Through constant iterative optimization, the relevant functional modules have been further improved. RESULTS AND CONCLUSIONS: After a 1-year clinical trial, app functions have stabilized, fulfilling the expectations of technicians and boosting the operating efficiency of clinical practices. In comparison with traditional methods, the app allows for easy access to patient information; rapidly reviewed, synchronous cataloguing; and convenient retrieval. Further exploration is warranted.